(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
Diffuse-toxic goiter is an organospecific autoimmune disease characterized by increased secretion of thyroid hormones T3 and T4 and changes in the nervous system and cardiovascular system. It occurs mainly in the age group of 20-50 years, more in women than in men. The incidence ratio of women to men is 10:1